An approach for identification of ultrahigh energy extensive air showers with scintillation detectors at TAIGA experiment - Astapov, I.; Bezyazeekov, P.; Gafarov, A.; Garmash, A.; Grebenyuk, V.; Gress, O.; Gress, T.; Grishin, O.; Grinyuk, A.; Horns, D.; Ivanova, A.; Kalmykov, N.; et al. (Journal of Instrumentation, 2020)
The TAIGA astroparticle observatory is under development at Tunka valley close to the Baikal Lake. This simulation study is concentrated on the ultrahigh energy extensive air showers (EAS) induced by gamma-quanta or proton in the range from 1 PeV to 10 PeV and zenith angle ranging 0°–45°. For this work, a set of air showers was created by CORSIKA software package. The list of useful secondary particles at the ground level is produced using the COAST library package. The interaction of secondary particles with the soil and detectors was simulated with GEANT4 package. The method based on neural network has been developed for the separation of EAS induced by gamma-quanta or proton. The air showers having energy ranging 1–10 PeV show more than 90% of identification efficiency of protons while keeping identification efficiency of gamma around 50% or more.